2010
DOI: 10.1096/fj.10-171959
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning the stimulation of MLL1 methyltransferase activity by a histone H3‐based peptide mimetic

Abstract: The SET1 family of methyltransferases carries out the bulk of histone H3 Lys-4 methylation in vivo. One of the common features of this family is the regulation of their methyltransferase activity by a tripartite complex composed of WDR5, RbBP5, and Ash2L. To selectively probe the role of the SET1 family of methyltransferases, we have developed a library of histone H3 peptide mimetics and report herein the characterization of an Nα acetylated form of histone H3 peptide (NαH3). Binding and inhibition studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…To define the minimal structural determinants recognized by RcATXR5, enzymatic assays were performed as previously described (37, 38). Briefly, 600nM of enzyme was incubated with 1mM of peptide in the HMT buffer during 1 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To define the minimal structural determinants recognized by RcATXR5, enzymatic assays were performed as previously described (37, 38). Briefly, 600nM of enzyme was incubated with 1mM of peptide in the HMT buffer during 1 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 600nM of enzyme was incubated with 1mM of peptide in the HMT buffer during 1 h at 30°C. Reactions were stopped and activity was quantified by liquid scintillation counts as previously described (37, 38). The kinetic parameters for the methylation of H3.1 (KQLATKAARKSAPATGGVKY) and H3.3 (KQLATKAARKSAPTTGGVKY) by RcATXR5 were measured using purified recombinant RcATXR5 and synthetic H3 peptides (GenScript).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic assays of ATXR5 SET domain on histone peptides were performed by scintillography as previously described (8,22,23). Methyltransferase assays performed on octamer and nucleosomes substrates were prepared as follow.…”
Section: Methodsmentioning
confidence: 99%
“…Methyltransferase assays were performed with the nucleosome core particles or octamers at 0.2 μM, increasing amounts of ATXR5 full-length, ATXR5 L39W or ATXR5 ΔPHD (0.375, 0.75, 1.5 μM), 1.8 μM radiolabeled [ 3 H- methyl ]-AdoMet in buffer containing 50 mM Tris (pH 8.5), 20 mM KCl, 10 mM MgCl 2 , 10 mM β-mercaptoethanol and 10% glycerol in a final volume of 30 μl at 30°C for 1 h. Reactions were stopped by boiling in SDS-PAGE sample buffer and separated by SDS-PAGE. The gels were treated for scintillation, dried, autoradiographed and quantified as previously described (8,22,23). …”
Section: Methodsmentioning
confidence: 99%
“…However, therapeutic effects of this inhibitor could not be demonstrateddneither in vitro nor in vivo (178). The same group has previously shown that the inhibition of MLL1 is also possible by targeting the interaction between histone H3 and MLL1 with an acetylated H3-based peptide (179).…”
Section: Inhibitors Of Mll1mentioning
confidence: 99%